Pengaruh Tingkat Pengangguran, Pertumbuhan Ekonomi, dan Inflasi Terhadap Tingkat Kemiskinan pada Provinsi Regional Sumatera - Asmadia, Tezi; Andriany, Vicy; Sani, Muhammad Syaiful (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
The main problem in this reserch is that unemployment, economic growth and inflation influence poverty, but the data found fluctuates. The purpose of this discussion is to analyze how much the unemployment rate, economic growth and inflation influence the poverty level in provinces in the Sumatra region. This type of research is quantitative. The data collection technique used is documentation. The data analysis techniques used in this test are multiple linear regression analysis, classical assumption testing, and hypothesis testing with the help of the SPSS Version 25 program. From the research conducted by researchers, it can be concluded that the unemployment variable has a significant effect on poverty levels. Meanwhile, the variables economic growth and inflation do not have a significant effect on the poverty level. However, based on joint tests, it shows that unemployment, economic growth and inflation do not have a significant effect on the poverty level which is caused by the weak influence of the independent variables on the dependent variable and the presence of other factors that are more influential such as the level of education, health and access to infrastructure.